Studi Literatur: Perbandingan Peanut Ball Dan Birthing ball Terhadap Kemajuan Persalinan kala I Fase Aktif - fifi ishak (Program Studi Ilmu Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Indonesia Timur, 2021)
The progress of labor in the first stage of the active phase is the most tiring, heavy, and where most mothers begin to feel pain or tenderness. In this phase most mothers feel great pain because the activities of the uterus that begins to be more active. This literature research aims to determine the comparison of Peanut Ball and Birthing ball to the Progress of Stage 1 Labor in the Active Phase of Maternity .This research method is a literature study or literature review,The data collection technique used in this study is by searching for research journals published on the internet using google scholar, PubMed, and Garuda Portal. Based on several journals that have been discussed here. it can be concluded that there is a comparison of the use of the peanut ball and birthing ball in mothers who give birth during the first active phase.